Model the Effect Community Trust, Financial Organizational, Leadership on Organizational Performance: Empiric Study in Boarding Schools - Agustian Zen; Hapzi Ali; Dewi Puspaningtyas Faeni (International Journal of Global Sustainable Research, 2023)
The purpose of this study is to prove whether from each variable there is an influence with independent variables with data processing in the object of research. This study used a survey method.  The population in this study is the Head of Boarding Schools (Mudir) in West Java domestic as many as 56 Heads of Islamic Boarding Schools (Mudir), with purposive Sampling and data Analysis Techniques using simple regression analysis assisted by SPSS version 24. variability of community trust with Organizational Performance has a significant influence, the third test with the results that financial organization has a significant influence on Organizational Performance, Leadership with Organizational Performance has a significant influence, and testing together found that 58.8% is significant and positive. The results of this study are just the beginning and can be continued in other studies added with other variables with the same or other objects.